2008
DOI: 10.1007/s00423-008-0307-5
|View full text |Cite
|
Sign up to set email alerts
|

Results of surgery for colorectal carcinoma with obstruction

Abstract: Obstructing colorectal carcinoma seems to be associated with high mortality rate, but long-term survival seems to be the same with non-obstructing carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
4
17
0
2
Order By: Relevance
“…Mean follow up time was 6.31 months. [33,34] Several studies have found similar disease-specific survival rate for elderly and young colorectal cancer patients, [35,36] but differences in overall survival, indicating that increased mortality in oncogeriatric patients was due to competing cause of death and not to CRC. Therefore, decreased survival in the elderly is mainly due to differences in early mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Mean follow up time was 6.31 months. [33,34] Several studies have found similar disease-specific survival rate for elderly and young colorectal cancer patients, [35,36] but differences in overall survival, indicating that increased mortality in oncogeriatric patients was due to competing cause of death and not to CRC. Therefore, decreased survival in the elderly is mainly due to differences in early mortality.…”
Section: Discussionmentioning
confidence: 99%
“…ReFeRÊNCIAs O número médio de linfonodos dissecados foi semelhante em ambos os grupos e acima dos 12 linfonodos, padronizados atualmente como mínimo necessário a uma linfadenectomia adequada, demonstrando o critério oncológico adotado nas cirurgias realizadas nos dois grupos, também de acordo com os dados encontrados na literatura 8,9,11,12,15,16,20,21 . A incidência de complicações pós-operatórias foi semelhante nos grupos estudados 7 , sendo maior do que a média relatada na literatura internacional 20 , possivelmente como reflexo de intervenções cirúrgicas em pacientes portadores de lesões avançadas, com menor performance status e pior condição nutricional.…”
Section: Discussionunclassified
“…Em países desenvolvidos, mais de um terço dos pacientes são diagnosticados através de testes de screening populacionais. Nesses países, em séries históri-cas, mesmo após a apresentação de sintomas, cerca de 80% dos casos são operados eletivamente [5][6][7] . Tais dados se contrapõem aos da literatura latino-americana, na qual se apresentam taxas mais altas de pacientes operados em fases avançadas da doença, muitos dos quais em caráter de urgência 8,9 .…”
Section: Introductionunclassified
“…While some studies have reported that OCRC has a poorer prognosis than nonobstructing CRC, 4,5 others have found no difference. 6,7 This poses a problem in the surgical management of OCRC.In many institutions, 1-stage primary resection is recommended for OCRC, as this allows colostomy and further nonsurgical drainage for the obstruction to be avoided. [8][9][10] On the other hand, disruption of anastomosis was observed in more than 50% of cases in which resection was performed as initial surgery without surgical or nonsurgical decompression for the obstruction, threatening overall deterioration in the patient's condition.…”
mentioning
confidence: 99%
“…[1][2][3] While some studies have reported that OCRC has a poorer prognosis than nonobstructing CRC, 4,5 others have found no difference. 6,7 This poses a problem in the surgical management of OCRC.…”
mentioning
confidence: 99%